The relationship of food, water intake and esthetic changes during pregnancy - Priscila Couto Menna; Diogo Thimoteo da Cunha; Cezar Henrique de Azevedo (O Mundo da Saúde)
The most notable esthetic alterations observed during pregnancy occur to the skin, with an increase in thickness due to edema. It is believed that these problems are triggered and/or aggravated due to the small intake of some food items. The objective of this study was to evaluate the relationship of food consumption, water intake and the appearance of cutaneous and vascular alterations in pregnant women. Pregnant women participating in health programs in the municipality of Santos were enrolled, and answered questionnaires to verify healthy practices and attitudes, water intake and esthetic problems – cellulitis, striae, periorbital dark circles and varicose veins. To evaluate food consumption, a food frequency questionnaire (FFQ) adjusted for the study purpose was used. The sample was grouped in tertiles for food consumption and water intake related to each esthetic problem for performance of logistic regression models. 105 pregnant women at the mean age of 24.4 years participated in the study. The relationship between the consumption of food items which are source of protein, vitamin C and calcium were found as protective factors for striae (OR 0.62) in the tertile of highest consumption, as well as water intake for tertiles 2 (OR 0.62) and 3 (OR 0.61). As for varicose veins, cellulitis and periorbital dark circles this relationship was not statistically significant. It was observed that diets rich in protein, vitamin C, calcium and water intake (more than four glasses per day) was a protective factor against the appearance of striae in pregnant women.